Penerapan Model Problem Based Learning Dalam Meningkatkan Hasil Belajar Ekonomi Kelas X3 SMA Negeri 9 Bulukumba - naisyah, naisyah (Universitas Negeri Makassar, 2019)
This study aims to determine the results of economic learning using the problem based learning (PBL) learning model. The research method used is the classroom Action Research through four stages, namely: action planning, action, observation, and reflection. Data collection is done by test and observation techniques. From the results of the research and data analysis, it was concluded that the application of the problem based learning (PBL) learning model especially in the consumption and investment material for class X3 in Bulukumba State High School 9 increased. For this reason, innovations in learning need to be continuously improved and supported by the provision of adequate educational facilities